Utilization of Peanut Shell Waste (Arachis hypogaea) As a Growth Media for Probiotic Bacteria Streptococcus thermophiles - Suwasdi Suwasdi; Mahdalina Mursilati; Surya Bagus; Monica Sonia Indri Pradipta; Esna Dilli Novianto (Universitas Tidar, 2019)
The increasing demand for peanut-based snacks has an impact on increasing peanut shell waste in Indonesia. The cellulose content in peanut shells is still relatively high, so it requires a long period for natural degradation. Though the waste can be converted and utilized in other forms, as a prebiotic. This far, inulin has been used as a prebiotic source. Products with inulin fortification have high prices, so we need to look for other cheaper ingredients. This research was conducted to test the ability of peanut shell waste extract as a prebiotic substitute material. To achieve this goal, peanut shells were extracted for cellulose. Streptococcus thermophiles probiotic bacterial growth test performed with a completely randomized design (CRD) pattern. The treatment factor used was crude extracts concentration of peanut shell waste. 0% was for the negative control, 20%, 40%, 60%, 80% and inulin were for positive control. Observation parameters in the research were the identification of colony morphology, gram staining, and growth curve analysis. The results of the study showed the crude extract of peanut shell waste affected Streptococcus thermophiles growth rate, even though it was not equivalent to the results of inulin treatment. The addition of coarse peel extract (40%) showed the most optimal growth curve pattern. The cellulose from peanut waste used as a carbon source for bacteria growth.Keywords: Peanut shell, prebiotics, Streptococcus thermophilus